Model to Model Transformation for Declarative Models - Aggarwal, Alok; Dixit, S; Agarwal, Smita (International Journal of Computer Sciences and Engineering, 2025)
In Model Driven Architecture (MDA), model and meta-model are the primary artifacts. In this work, a detailed analysis of the existing meta-model-based transformation tools is done for the declarative model using an exhaustive criterion. The evaluation of the eleven chosen tools, which are open source and has download page available using search engine like Google Scholar and Github, is analyzed; like UML–RSDS, Tefkat, JTL, PTL etc. Analysis is performed over fourteen different parameters like language, model query, type of transformation, compatibility, cardinality etc. Results show that all selected tools produce platform specific target model which mostly transform PSM to PSM and none produces platform independent target model transforming a PSM into PIM.